Reinvesting in families : strengthening child welfare practice for a brighter future : voices from the prairies - Badry, Dorothy Eleanor, 1958-; McKay, Sharon, 1940-; Fuchs, Don, 1948-; Montgomery, H. Monty, 1962- (University of Regina Press, 2014)
Reinvesting in Families addresses tough issues such as FASD, high-risk substance misuse, and family reunification from a family-focused and First Nations perspective. With a focus on the Prairies, it offers insight to anyone anywhere with an interest in child welfare service, research, and practice.